Macroeconomic determinants of housing prices in Malaysia / Nur Amaleena Najwa Hasan Basri - Hasan Basri, Nur Amaleena Najwa (2015)
Over the few years, house price in Malaysia has experienced significant price expansion and it became a worrying trend for lenders. This study is an attempt to identify the macroeconomic determinants of housing prices in Malaysia from year1984 until year 2013. There are total of four macroeconomics variables which are Gross Domestic Product (GDP), Inflation Rate (I), Population (P) and Interest Rate(R) were taken into study together with Housing Price Index (HPI). The design of this study comprises of 30 secondary data of each variables from year 1984 until year 2013 which are in yearly basis. In the process of findings, the researcher is using EViews7 software to generate all the data for analysis purposes. The result indicates that only three out of four predictors are significantly related to the movement of House Price Index (HPI). The overall study intends to contribute and enhance the speculators, investors, buyers and policy makers in their decision making based on the unpredictable rise of house price in Malaysia.